Morphological and Molecular Data Reveal Three Distinct Populations of Indian Wild Rice Oryza rufipogon Griff. Species Complex - Singh, Balwant; Singh, Nisha; Mishra, Shefali; Tripathi, Kabita; Singh, Bikram P.; Rai, Vandna; Singh, Ashok K.; Singh, Nagendra K. (Frontiers in Plant Science, 2018)
Wild relatives of crops possess adaptive mutations for agronomically important traits, which could play significant role in crop improvement for sustainable agriculture. However, global climate change and human activities pose serious threats to the natural habitats leading to erosion of genetic diversity of wild rice populations. The purpose of this study was to explore and characterize India’s huge untapped wild rice diversity in Oryza rufipogon Griff. species complex from a wide range of ecological niches. We made strategic expeditions around diversity hot spots in 64 districts of nine different agro-climatic zones of the country and collected 418 wild rice accessions. Significant variation was observed among the accessions for 46 morphological descriptors, allowing classification into O. nivara, O. rufipogon, and O. sativa f. spontanea morpho-taxonomic groups. Genome-specific pSINE1 markers confirmed all the accessions having AA genome, which were further classified using ecotype-specific pSINE1 markers into annual, perennial, intermediate, and an unknown type. Principal component analysis revealed continuous variation for the morphological traits in each ecotype group. Genetic diversity analysis based on multi-allelic SSR markers clustered these accessions into three major groups and analysis of molecular variance for nine agro-climatic zones showed that 68% of the genetic variation was inherent amongst individuals while only 11% of the variation separated the zones, though there was significant correlation between genetic and spatial distances of the accessions. Model based population structure analysis using genome wide bi-allelic SNP markers revealed three sub-populations designated ‘Pro-Indica,’ ‘Pro-Aus,’ and ‘Mid-Gangetic,’ which showed poor correspondence with the morpho-taxonomic classification or pSINE1 ecotypes. There was Pan-India distribution of the ‘Pro-Indica’ and ‘Pro-Aus’ sub-populations across agro-climatic zones, indicating a more fundamental grouping based on the ancestry closely related to ‘Indica’ and ‘Aus’ groups of rice cultivars. The Pro-Indica population has substantial presence in the Eastern Himalayan Region and Lower Gangetic Plains, whereas ‘Pro-Aus’ sub-population was predominant in the Upper Gangetic Plains, Western Himalayan Region, Gujarat Plains and Hills, and Western Coastal Plains. In contrast ‘Mid-Gangetic’ population was largely concentrated in the Mid Gangetic Plains. The information presented here will be useful in the utilization of wild rice resources for varietal improvement.